Pemodelan Riset Hukum: Analisis Corak Hukum Lingkungan di Indonesia : PEMODELAN RISET HUKUM: ANALISIS CORAK HUKUM LINGKUNGAN DI INDONESIA - Isman, Isman; Novita, Novita (Fakultas Hukum Universitas Jambi, 2024)
This research explores modeling in environmental administrative law research, specifically the idealization of legal situations or phenomena, environmental law policy analysis, and specific contexts of environmental administrative law. This research is conducted through a library research approach that utilizes data from Scopus-indexed journal articles from 2022-2024. The analysis focuses on identifying trends, changes, and patterns in various fields of environmental administration law. The modeling research findings offer detailed insights into the dynamics of legal evolution, contributing to formulating policies that respond to complex environmental changes. The research concludes that the evolution of legal ideals and their contexts significantly influence preventive, repressive, curative, and rehabilitative legal research modeling.